ENT600 : Company analysis Proton Holdings Berhad / Jessica Joseph, Edzatul Noradiah Durimi and Mohd Subky Ismail - Joseph, Jessica; Durimi, Edzatul Noradiah; Ismail, Mohd Subky (2017)
Malaysia's car industry is dominated by two local manufacturers which are supported by the government through its National Car Policy. These local manufacturers are Proton and Perodua. Proton was the first local company car's established in Malaysia which dominated not only domestic market but also the international markets. From the first year of sales until the present years, it is seen that Proton has been through a lot in terms of services and sales inside automotive arena. The company have gained profit and faced loss during its operation. Proton being as the national car maker, is still lacked behind compared to other car makers on the international stage. The cheap price of Proton cars came at a costly tradeoff against quality and safety. Although Proton cars are much cheaper than foreign cars, most local preferred to buy other car brands which is reliable, have good performance and best quality. Also, the lack of competition during the early days of government protection has led Proton to produce obsolete design that lack of current safety features.